Evaluating the Internal Marketing of Handicraft MSMEs' Development Based on the Hexahelix Model - Depy Muhamad Pauzy; Ristina Siti Sundari; Mehmet Gökhan Özdemir (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The handicraft sector in Rajapolah, Tasikmalaya, faced significant challenges during the coronavirus disease 2019 pandemic, impacting the economic resilience of micro, small, and medium enterprises. This study aims to evaluate how internal marketing practices, integrated with the Hexahelix model involving academia, business, community, government, media, and investors, enhance the development of these enterprises in a regional context. Employing a qualitative descriptive approach, data were collected through semi-structured interviews, observations, and document analysis from nine handicraft enterprises in Rajapolah. The findings reveal that academia, business, community, government, and media significantly contribute to internal marketing by supporting employee training, digital promotion, and market access, whereas investor engagement remains limited due to perceived risks. Effective stakeholder collaboration, particularly through digitalization and local exhibitions, improves product quality and brand visibility. This study concludes that integrating internal marketing with the Hexahelix model fosters sustainable development for handicraft enterprises, though strategies to engage investors are needed to ensure scalability.